2017
DOI: 10.2139/ssrn.2953611
|View full text |Cite
|
Sign up to set email alerts
|

Low-Latency Trading and Price Discovery: Evidence from the Tokyo Stock Exchange in the Pre-Opening and Opening Periods

Abstract: We study whether the presence of low-latency traders (including high-frequency traders (HFTs)) in the pre-opening period contributes to market quality, defined by price discovery and liquidity provision, in the opening auction. We use a unique dataset from the Tokyo Stock Exchange (TSE) based on server-IDs and find that HFTs dynamically alter their presence in different stocks and on different days. In spite of the lack of immediate execution, about one quarter of HFTs participate in the pre-opening period, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This also happens for other assets either at the opening or closing auctions. According Bellia et al (2016), cancellations near auction ending time are mostly due to high-frequency traders. The behavior of this quantity on US exchanges is markedly different from that of Paris Stock Exchange for which Challet (2019) finds that the number of events increases as a power-law until the auction time.…”
Section: Typical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…This also happens for other assets either at the opening or closing auctions. According Bellia et al (2016), cancellations near auction ending time are mostly due to high-frequency traders. The behavior of this quantity on US exchanges is markedly different from that of Paris Stock Exchange for which Challet (2019) finds that the number of events increases as a power-law until the auction time.…”
Section: Typical Activitymentioning
confidence: 99%
“…More recently, and more in line with our paper, Boussetta et al (2016) study the French Stock exchange and find that different kind of market participants enter the pre-auction periods at markedly different times, the slow brokers acting first, while high-frequency traders tend to be active nearer the end of auctions. In the same vein, Bellia et al (2016) show how and when low-latency traders (identified as high frequency traders) add or remove liquidity in the pre-opening auction of the Tokyo Stock Exchange. Lehalle and Laruelle (2018) devote part of a chapter to auctions in a spirit close to ours, in particular regarding typical daily activity patterns.…”
Section: Introductionmentioning
confidence: 99%